Preparation of the Future Teachers of Kindergartento the Forming of Moral Base of Pupil’s Personality - Dobosh, Olena (Pedagogical Discourse, 2012)
The methodical approaches to professional preparation of the future teachers of Ukrainian kindergartens are analyzed in the article. The professional forming of children’s ethical skills in the period of sensitive developing of their personality is defined.